Proof of the Riemann Hypothesis - (:unkn) unknown (My University, 2020)
We show initially in this article that the function (Zeta) Riemann and analytic continuation we call ℵ are distinct. Later we show that this extension on ℂ indeed has zeros on the critical line ℜ() = 1 2 and they are the only known non-trivial zeros. The Riemann Hypothesis says: All non-trivial zeros of the function () are located on the right complex () é() = 1 2 A-On the analytical continuation of the function The analytic continuation of the function () be called ℵ to distinguish it from the Riemann function. The Riemann function is written: () = ∑ 1 ∞ =1
Keywords: African Research